MG53, A Novel Regulator of KChIP2 and Ito, f, Plays a Critical Role in Electrophysiological Remodeling in Cardiac Hypertrophy. Issue 18 (30th April 2019) - Liu, Wenjuan; Wang, Gang; Zhang, Cuicui; Ding, Wenwen; Cheng, Wanwen; Luo, Yizhi; Wei, Chaoliang; Liu, Jie
Abstract : Background: KChIP2 (K + channel interacting protein) is the auxiliary subunit of the fast transient outward K + current ( I to, f ) in the heart, and insufficient KChIP2 expression induces I to, f downregulation and arrhythmogenesis in cardiac hypertrophy. Studies have shown muscle-specific mitsugumin 53 (MG53) has promiscuity of function in the context of normal and diseased heart. This study investigates the possible roles of cardiac MG53 in regulation of KChIP2 expression and I to, f, and the arrhythmogenic potential in hypertrophy. Methods: MG53 expression is manipulated by genetic ablation of MG53 in mice and adenoviral overexpression or knockdown of MG53 by RNA interference in cultured neonatal rat ventricular myocytes. Cardiomyocyte hypertrophy is produced by phenylephrine stimulation in neonatal rat ventricular myocytes, and pressure overload-induced mouse cardiac hypertrophy is produced by transverse aortic constriction. Results: KChIP2 expression and I to, f density are downregulated in hearts from MG53-knockout mice and MG53-knockdown neonatal rat ventricular myocytes, but upregulated in MG53-overexpressing cells. In phenylephrine-induced cardiomyocyte hypertrophy, MG53 expression is reduced with concomitant downregulation of KChIP2 and I to, f, which can be reversed by MG53 overexpression, but exaggerated by MG53 knockdown. MG53 knockout enhances I to, f remodeling and action potential duration prolongation and increases susceptibility to ventricular arrhythmia in mouse cardiac hypertrophy. Mechanistically, MG53 regulates NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) activity and subsequently controls KChIP2 transcription. Chromatin immunoprecipitation demonstrates NF-κB protein has interaction with KChIP2 gene. MG53 overexpression decreases, whereas MG53 knockdown increases NF-κB enrichment at the 5' regulatory region of KChIP2 gene. Normalizing NF-κB activity reverses the alterations in KChIP2 in MG53-overexpressing or knockdown cells. Coimmunoprecipitation and Western blotting assays demonstrate MG53 has physical interaction with TAK1 (transforming growth factor-b [TGFb]-activated kinase 1) and IκBα (nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha), critical components of the NF-κB pathway. Conclusions: These findings establish MG53 as a novel regulator of KChIP2 and I to, f by modulating NF-κB activity and reveal its critical role in electrophysiological remodeling in cardiac hypertrophy. Abstract : Supplemental Digital Content is available in the text.